A Christmas story - Brown, Leigh; Clark, Bob.; Dupont, Rene.; Sheperd, Jean.; Metro-Goldwyn-Mayer. ([New York] MGM/UA Video, 1983)
All Ralphie Parker wants for christmas is a genuine Red Ryder carbine action two hundred shot lightning loader range model air rifle.
VHS
Based on the novel, In God we Trust, All Others Pay Cash, by Jean Sheperd.
Film editor, Stan Cole.
Melinda Dillon, Darren McGawn, Peter Billingsley.
Keywords: Feature films; Comedy films